Women's abortion seeking behavior under restrictive abortion laws in Mexico. - Fatima Juarez; Akinrinola Bankole; Jose Luis Palma (PLoS ONE)
Abortion is regulated in Mexico at the state level, and it is permitted under certain criteria in all 32 states, except in Mexico City where first-trimester abortion is decriminalized. Yet, more than a million abortions occur in Mexico each year. But most terminations occurring outside of Mexico City are clandestine and unsafe due to profound stigma against the procedure, lack of trained providers, lack of knowledge of where to find a safe abortion and poor knowledge of the laws. While this situation is moderated by the increasing use of misoprostol, a relatively safe method of abortion, the safety of the procedure cannot be assured in restrictive legal contexts. The purpose of this study is to explore women's experiences with induced abortion in three federal entities with different legal contexts, and whether abortion seeking behavior and experiences differ across these settings. The study was carried out in three states, representing three different degrees of restrictiveness of abortion legislation. Queretaro with the "most restrictive" law, Tabasco with a "moderately restrictive" law, and Mexico state with the "least restrictive" law. We hypothesize that women living in more restrictive states will resort to the use of more unsafe and risky methods and providers for their abortion than their counterparts in less restrictive states. Women who recently obtained abortions were selected through snowball sampling and qualitative data were collected from them using semi-structured indepth interviews. Data collection took place between mid-2014 and mid-2015, with a final sample size N = 60 (20 from each state). Various themes involved in the process of abortion seeking behavior were developed from the IDIs and examined here: women's knowledge of the abortion law in their state, reasons for having an abortion; the methods and providers used and women's positive and negative experiences with abortion methods and providers used. Our results indicate that abortion safety is not associated with the restrictiveness of abortion legislation. Findings show that there is a new pattern of abortion service provision in Mexico, with misoprostol, a relatively safe and easy to use method, playing an important role. Nevertheless, while access to misoprostol tends to increase the safety of abortion, the improvement is moderated by women and their informants (relatives, friends and partners) not having accurate information on how to safely self-induce an abortion with misoprostol. On the other hand, some women manage to have safe abortion in illegal setting by going to Mexico City or with the support of NGOs knowlegeable on abortion. Findings demonstrate the importance of decriminalization of abortion, but meanwhile, harm reduction strategies, including promotion of accurate information about self-use of misoprostol where abortion is legally restricted will result in safe abortion.